Design of a Phenotypic Sensor About Protein and Moisture in Wheat Grain - Liu, Yiming; Li, Donghang; Li, Huaiming; Jiang, Xiaoping; Zhu, Yan; Cao, Weixing; Ni, Jun (Frontiers in Plant Science, 2022)
A near-infrared spectrometer can perceive the change in characteristics of the grain reflectance spectrum quickly and nondestructively, which can be used to determine grain quality information. The full-band spectral information of samples of multiple physical states can be measured using existing instruments, yet it is difficult for the full-band instrument to be widely used in grain quality detection due to its high price, large size, non-portability, and inability to directly output the grain quality information. Because of the above problems, a phenotypic sensor about grain quality was developed for wheat, and four wavelengths were chosen. The interference of noise signals such as ambient light was eliminated by the phenotypic sensor using the modulated light signal and closed sample pool, the shape and size of the incident light spot of the light source were determined according to the requirement for collecting the reflectance spectrum of the grain, and the luminous units of the light source with stable light intensity and balanced luminescence were developed. Moreover, the sensor extracted the reflectance spectrum information using a weak optical signal conditioning circuit, which improved the resolution of the reflectance signal. A grain quality prediction model was created based on the actual moisture and protein content of grain obtained through Physico-chemical analyses. The calibration test showed that the R2 of the relative diffuse reflectance of all four wavelengths of the phenotypic sensor and the reflectance of the diffusion fabrics were higher than 0.99. In the noise level and repeatability tests, the standard deviations of the relative diffuse reflectance of two types of wheat measured by the sensor were much lower than 1.0%, indicating that the sensor could accurately collect the relative diffuse reflectance of wheat. In the calibration test, the root mean square errors of protein and moisture content of wheat in the Test set were 0.4866% and 0.2161%, the mean absolute errors were 0.6515% and 0.3078%, respectively. The results showed that the near-infrared phenotypic sensor about grain quality developed in this study could be used to collect the diffuse reflectance of grains and the moisture and protein content in real-time.